Enhancing the public health impact of latent tuberculosis infection diagnosis and treatment (ACT4): protocol for a cluster randomised trial. Issue 3 (20th March 2019) - Oxlade, Olivia; Trajman, Anete; Benedetti, Andrea; Adjobimey, Mênonli; Cook, Victoria J; Fisher, Dina; Fox, Gregory James; Fregonese, Federica; Hadisoemarto, Panji; Hill, Philip C; Johnston, James; Long, Richard; et al.
Abstract : Introduction: Treatment of latent tuberculosis (TB) infection (LTBI) is an important component of the End-TB strategy. However, the number of individuals who successfully complete LTBI treatment remains low as there are losses at all steps in the LTBI 'cascade-of-care'. The reasons for these losses are variable and highly dependent on the setting. We have planned a trial of a standardised public health approach to strengthen the management of household contacts (HHCs) of newly diagnosed patients with pulmonary TB. Assessing costs related to approach is a secondary objective of the study. Methods and analysis: A cluster randomised trial will be conducted in 24 randomisation units (health facilities or groups of health facilities) in five countries. In Phase 1, at intervention sites, we will conduct a standardised assessment of the current LTBI programme, with a focus on cascade-of-care endpoints. Standardised open-ended questionnaires on practices, knowledge, attitudes and beliefs regarding TB prevention are then administered to key patient groups and healthcare workers. At each site, local stake-holders will review study findings and select solutions based on their acceptability, cost and effectiveness. In Phase 2, intervention clinics will implement the selected solutions, along with contact measurement registries and regular in-service LTBI management training. Control sites will continue their usual LTBI care with no explicit evaluation, strengthening or training activities. The primary study outcome is the number of HHC initiating LTBI treatment per newly diagnosed active TB patient, within 3 months of diagnosis of the index patient. An intention-to-treat analysis will be performed, using a Poisson regression approach. Ethics and dissemination: Ethics approval from the MUHC ethical review board (ERB) was obtained in November 2015. During the study standardised tools will be developed and made publicly available. Key study findings and novel methodologic contributions will be detailed in publications and other dissemination activities. Trial registration number: NCT02810678 ; Pre-Results.